The U.S. Assistance to the MENA Arab Countries under the Trump Administration: The Logic of a Diff erentiated Approach - V. I. Bartenev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
This paper identifi es and explains key changes in the U.S. aid policies towards Arab countries of the Middle East and North Africa (MENA) under Donald Trump. It seeks to validate two widespread arguments — the one about the current administration’s revision of pivotal principles of providing foreign assistance, and the other one — about an accelerated disengagement of the United States from the MENA region since 2017. The paper consists of four sections. The fi rst section explores the transformation of the U.S. strategic thinking and regional context under the Trump administration and then posits fi ve hypotheses about possible changes in the volume and composition of the U.S. assistance to the MENA region (in comparison with the fi nal two years of the Obama administration), as well as the diff erences in the executive branch and the Congress’s positions. The second section explains particularities of the statistical data and the methods of its exploration, the third section presents the results of hypothesis testing using aggregated data on aid fl ows to the region, and the fi nal section explains these results, sometimes unexpected, using the data disaggregated by country. Three of fi ve hypotheses proved wrong based on the aggregate data. First, the Trump administration did not cut assistance to the MENA more substantially than to other regions of the globe. Second, it did not ringfence aid accounts which helped yield direct dividends to the U.S. businesses. Third, the Republican Congress was clearly less willing to support the executive’s aid chocies under a new Republican President than during the last years of a Democrat Barack Obama’s second term. Only two hypotheses proved correct — one about a prioritization of security and military assistance under Donald Trump and the other one — about disproportionate cuts of democracy promotion assistance. Such an unexpected result calls for refi ning both aforementioned arguments and taking into account the dissimilarities in the dynamics of assistance to diff erent countries. The United States tends to practice a diff erentiated approach in dealing with two largest Arab aid recipients (Egypt and Jordan) and with other Arab countries. The assistance to Cairo and Amman is ringfenced and protected, while aid to other recipients, including security assistance and FMF grants, is prone to quite drastic cuts. This diff erentiation is explained by the fact that cooperation with Egypt and Jordan rests not only on more solid strategic foundations but also on a strong support within the United States — both from the defense contractors interested in large export contracts and from an infl uential pro-Israel lobby. The U.S. will not abandon this highly diff erentiated approach after the 2020 elections but the structure of assistance to the MENA region might undergo quite a dramatic transformation.